Social startup success : how the best nonprofits launch, scale up, and make a difference - Janus, Kathleen Kelly (New York, NY : Da Capo Lifelong, 2018)
Presents five key strategies responsible for the breakout growth of the most successful social startups: testing ideas, measuring impact, funding experimentation, leading collaboratively, and telling compelling stories.
Part 1. Testing ideas. The discovery phase -- Engaging all stakeholders -- Reframing failure as learning -- Part 2. Measuring impact. Crafting a compelling theory of change -- Maximizing use of data -- Making your data tell a story -- Part 3. Funding experimentation. Laying the foundation to experiment with earned income -- Testing earned income strategies -- Optimizing fundraising efforts -- Part 4. Leading collaboratively. Cultivating collective leadership -- Bringing in senior leadership early -- Building an active board -- Part 5. Telling compelling stories. Creating a compelling narrative -- Conclusion.
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Management; Social entrepreneurship; Business enterprises